A study of the Incidence of Cytomegalovirus infection and Preemptive Therapy in Kidney Transplant Recipients - M Saleem, Zana Sidiq; H Abd, Kais; Ibrahim, Nashwan M.R.; Hussein, Nawfal R; Al-Khammas, Hasanain MA (Journal of Contemporary Medical Sciences, 2022)
Objectives: This project aimed to determine the incidence of CVM infection and evaluate the outcome of preemptive treatment. Methods: This prospective, two centers cohort study included recipients who underwent renal transplant between May 2019-May 2020. The incidence of CMV infection and graft outcomes were studied. All managed with preemptive therapy. Results: In this study, 134 renal transplant recipients were recruited. Among them, 30/134 (22.4%) patients tested positive for CMV-RTPCR. We studied the impact of age on the CMV-positivity and we found that the age of the doner was associated with CMV-positivity (P= 0.025; OR= 0.923; CI= 0.8584-0.9943). Smoking and gender showed no association with CMV-positivity. Conclusions: our data suggest that the course of CMV infection is benign with a high success rate of preemptive treatment. Further evaluation for the universal prophylactic plan is needed.